(untitled) (Global Journal of Medical Research, 2014)
Aim: A comparative study of immunohistochemical, hematoxylin eosin staining and its diagnostic importance in Hirschsprung’s disease. Material and Methods: The study of 510 patients comprised colorectal, appendicectomy biopsies and myectomy specimens at various levels. The study included both ganglionic and aganglionic segments of intestine. The specimens were fixed in 10% formalin solution. In the laboratory, the sections of paraffin embedded tissues were stained H E and compared with Cathepsin D; repeated sections were taken from these cases for the demonstration of H